2016
DOI: 10.18632/oncotarget.7785
|View full text |Cite
|
Sign up to set email alerts
|

The angiogenesis in decellularized scaffold-mediated the renal regeneration

Abstract: There are increasing numbers of patients underwent partial nephrectomy, and recovery of disturbed renal function is imperative post partial nephrectomy. We previously have demonstrated the decellularized (DC) scaffolds could mediate the residual kidney regeneration and thus improve disturbed renal function after partial nephrectomy. However, the cellular changes including the angiogenesis in the implanted DC scaffold has not yet been elaborated. In this study, we observed that the scaffold promoted the prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The other feasible one is orthotopically or heterotopically transplanting the complexes of cells and scaffolds, and then vessels would grow into the scaffold and supply nutrients and oxygen to cells. Unfortunately, previous research of our team 6 and other groups [16][17][18] suggest that few vessels or parenchymal cells but only inflammatory cells were found after a period of observation. And the speed of scaffold degradation was fast and unstable.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The other feasible one is orthotopically or heterotopically transplanting the complexes of cells and scaffolds, and then vessels would grow into the scaffold and supply nutrients and oxygen to cells. Unfortunately, previous research of our team 6 and other groups [16][17][18] suggest that few vessels or parenchymal cells but only inflammatory cells were found after a period of observation. And the speed of scaffold degradation was fast and unstable.…”
Section: Discussionmentioning
confidence: 77%
“…However, liver parenchyma cells did not migrate into the scaffold as expected. Another similar research with the usage of decellularized kidney scaffolds has also suggested that the grafted kidney scaffold just degenerates rather than facilitates renal stem cells to migrate into the matrix …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Data from radionuclide renogram demonstrated enhanced restoration of renal functions. Based on these observations and relying on previous insights [16, 17], we speculated that the intensity of angiogenesis may promote renal regeneration. Impaired organs may be repaired by seeded endothelial cells to help repairing vessels, hence, organs [18].…”
Section: Discussionmentioning
confidence: 78%
“…Gels derived from dECM bladder were prepared as stated earlier in 24‐well plates. HUVECs were chosen as an ideal human cell type for testing due to their extensive usage in tissue engineering applications with decellularized scaffolds to promote angiogenesis and tissue regeneration . HUVECs were seeded at a density of 40,000 cells per well and cultured for 72 h. For live‐dead staining and microscopy, cells were incubated with 2 µM Calcein AM live stain and 4 µM EthD‐1 dead stain in PBS (1×; pH 7.4) with calcium and magnesium for 45 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%